Macroeconomic aspects of structural labor market reforms in Germany - Jonas Dovern; Carsten-Patrick Meier (Kiel Institute for the World Economy (IfW), 2006)
Using a newly constructed macroeconometric model for Germany and the rest of the Euro area, we investigate the macroeconomic effects of structural labor market reforms in Germany. We find that neither the fact that Germany can no longer pursue an independent monetary policy nor the possibility that other countries in the Euro area might react to reforms in Germany by implementing labor market reforms themselves constitute impediments to successful reforms. Reforms would relative quickly bring down unemployment and increase GDP significantly. Even former labor market "insiders" would gain as net wages increase due to falling unemployment insurance contributions.
Keywords: E24; J64; 330; Macroeconometric model; Germany; Euro area; Labor market reforms; Arbeitsmarktpolitik; Reform; Arbeitsmarktflexibilisierung; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Schätzung; Europäische Wirtschafts- und Währungsunion; Theorie; Deutschland